Comparación de las características del placer, según el Libro VI de la Ética Eudemia (Libro VII de la Ética Nicomáquea) y el Libro X de la Ética Nicomáquea - Solano Fallas, Andrés (2015)
In this article there will be a comparison of the characteristics of pleasure present in two of Aristotle’s ethical book, Book VI of Eudemian Ethics (EE) and Book X of Nicomachean Ethics (NE). This will be done from: 1) characteristics treated on Book VI of EE and kept in Book X of NE; 2) methodical corrections of some characteristics; and 3) the treatment of the term in both books.